2012
DOI: 10.17323/1995-459x.2012.3.6.15
|View full text |Cite
|
Sign up to set email alerts
|

A Rational Cluster Strategy: Manoeuvring between Market and Government Failures

Abstract: Вопрос о степени вмешательства государ-ства в кластерную сферу сохраняет свою актуальность. Однако развитие кла стеров не обеспечивается одними рыночными меха-низмами. В статье затронута проблема рисков, сни-жающих эффективность государственной политики, и приводятся рекомендации по их преодолению. рациональная кластерная стратегия:* Куценко евгений сергеевич -старший научный со-трудник, Центр научно-технической, инновационной и информационной политики, ИСИЭЗ НИУ ВШЭ. E-mail: ekutsenko@hse.ru Ключевые слова кл… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In the first case, the state becomes an initiator through financial support for their development. Such a viewpoint has been supported by some authors [94]; however, this policy is not always successful, as shown elsewhere [95]. In the second case, the clusters are developed by transnational companies together with regions.…”
Section: Cluster As a Model To Implement A Concept Of Open Innovation...mentioning
confidence: 91%
“…In the first case, the state becomes an initiator through financial support for their development. Such a viewpoint has been supported by some authors [94]; however, this policy is not always successful, as shown elsewhere [95]. In the second case, the clusters are developed by transnational companies together with regions.…”
Section: Cluster As a Model To Implement A Concept Of Open Innovation...mentioning
confidence: 91%
“…Moreover, cluster creation should not happen for political fashion`s sake, because a declaration about cluster creation doesn`t mean the organization of all conditions for its effective functioning. Actually, some clusters are just legal unions of separate companies without corresponding organizational content [1,6].…”
Section: Tpacee-201mentioning
confidence: 99%
“…Cluster-related efforts can improve the efficiency of economic agents via reinforced cooperation between companies, universities and R&D organizations; or between SMEs and corporations; or between private companies and infrastructure units. These efforts can help attracting foreign direct investment and integrating national producers into the global high-tech markets [Kutsenko, 2012]. For example, during the implementation of pilot innovative clusters support program in Russia between 2013 and 2015, the cluster member export revenues on average are 20% higher that the regional average 6 .…”
Section: Introductionmentioning
confidence: 99%